Em busca dos direitos: lutas e resistências do operariado têxtil cearense (anos 1940-1960) - Araújo, Jormana Maria Pereira (2018)
This thesis attempts to analyze the claims of textile working class in Ceará, especially of Cotonifício Leite Barbosa, during the years of re-democratization process in Brazil, between dictatorships. I defend that the textile working class searched to build an alternative project of industrialization in Ceará, which consider the worker dignity, expressed in social and work rights. In the middle the infrapolitics of the subordinate groups, the working class faced labormarket pressure, occasionally hidden way, and sometimes, in public and brutal ways. Faced the complexity of established relationships, it is used by theoretical and methodological arsenal the Social history of labour field. Among the main sources of research, the labor judiciary process and the newspapers which circulated in the capital of Ceará.